Steinbeck Center room - Doctor Paul Douglass:::Creator:::
Martha Heasley Cox Center for Steinbeck Studies in its fourth location, on the fifth floor of the Doctor Martin Luther King, Junior Library. This is the 'junk pile,' which showed various artifacts representing Cannery Row. These items were donated by Santa Barbara High School to the MHCCfSS in 1988. Most of this material was donated to the Monterey Maritime Museum July 2007. The Steinbeck Center has kept a small exhibit. Digital copy only. No hard copy.